DEVELOPMENT OF AUDITING OF AUDITING IN PRACTICAL LITERATES FROM FOREIGN LANGUAGE IN UKRAINIAN HIGHER EDUCATION - Кожем’яко H. (Proceedings of the National Aviation University. Series: Pedagogy, Psychology, 2019)
The article deals with listening as one of the most important components of speech competence and various ways of developing the skills of listening to practical classes in English. This skill is extremely relevant, as with the acceleration of scientific and technological progress, the transition to an information society in which perception and understanding of speech is one of the means of obtaining information when listening to news, viewing educational and entertainment television programs in foreign languages, feature films and documentaries, as well as during the conference, round tables, which is an extremely important tool in any field of human activity. The purpose of the article is to analyze the existing methods and approaches in the teaching of listening and to develop recommendations for the organization of training for listening to practical classes in a foreign language. Listening allows you to master the sound part of the language being studied, its phonemic component and intonation. It is through the audience that active learning of the lexical composition and its grammatical structure takes place. As a result of the constant training of this type of speech activity, logical thinking develops, as well as the ability to perform such complex mental operations as analysis, synthesis, deduction, comparison, specification, etc. Listening is one of the hardest types of speech activity. It is characterized by a one-time detection, so it’s important to learn how to perceive the text from the first time. Listening is not just a means of communication, but also preparation for an appropriate response at the beginning of information. It prepares speech, which helps to form the perception of speech by ear. The sequence of forming skills and skills to understand the speech on hearing is realized by doing exercises. According to the target orientation, the exercises are divided into two main groups: preparatory (training) and speech. Preparatory exercises do not teach listening, but form listening skills, promote the development of listening skills. Linguistic exercises are aimed at forming communicative competence and is a controlled speech activity. The ratio of preparatory and speech exercises varies depending on the level of knowledge of students, from the very stage of training. When exercising with an audition, you must adhere to a certain sequence, a gradual complication